Autoimmune hyperthyroidism and thyroid eye disease: what is the role of pro-oxidants and antioxidants?. (April 2015) - Kashkouli, Mohsen Bahmani; Aghamirsalim, Mohamadreza; Karimi, Naser; Shahrzad, Sahab
Abstract : There is a growing evidence that increased reactive oxygen generation plays an important role in pathogenesis of autoimmune disorders, including Graves' hyperthyroidism. It has been shown that decreased level of antioxidant vitamins (A, C and E) return to normal after the achievement of euthyroidism. Combined antioxidant treatment of patients with Graves' hyperthyroidism showed the same improvement effect as thyrostatic medications in terms of clinical symptoms. Thyroid eye disease (TED) is autoimmune in origin and does not result directly from endocrine hormonal imbalance. It has been proven that derangements of pro-/anti-oxidant enzymes occurs in TED and may stay for a long time after correction of hormonal imbalance. Increased levels of oxidative stress and decreased levels of the antioxidant reserve have been reported in the setting of TED. There are a few studies showing the beneficial effect of different singular or combined antioxidants treatment in patients with TED.